2020
DOI: 10.1017/s0007114520001932
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slow- v. fast-digested protein supplementation combined with mixed power training on muscle function and functional capacities in older men

Abstract: Aging leads to a progressive loss of muscle function (MF) and quality (MQ: muscle strength [MS]/lean muscle mass [LM]). Power training and protein (PROT) supplementation have been proposed as efficient interventions to improve MF and MQ. Discrepancies between results appear to be mainly related to the type and/or dose of proteins used. The present study aimed at determining whether or not mixed power training (MPT) combined with fast-digested PROT (F-PROT) leads to greater improvements in MF and MQ in elderly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 83 publications
(104 reference statements)
2
20
0
Order By: Relevance
“…Sixty‐six out of 74 studies were included in the lean body mass change analysis, utilizing 2665 subjects 33–99 . Six studies presented intervention groups not using RE training 41,46,94,97–99 ; of these, four studies tested protein ingestion exclusively, 41,97–99 and two studies tested protein ingestion in groups without and with resistance exercise 46,94 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixty‐six out of 74 studies were included in the lean body mass change analysis, utilizing 2665 subjects 33–99 . Six studies presented intervention groups not using RE training 41,46,94,97–99 ; of these, four studies tested protein ingestion exclusively, 41,97–99 and two studies tested protein ingestion in groups without and with resistance exercise 46,94 .…”
Section: Resultsmentioning
confidence: 99%
“…Six studies presented intervention groups not using RE training 41,46,94,97–99 ; of these, four studies tested protein ingestion exclusively, 41,97–99 and two studies tested protein ingestion in groups without and with resistance exercise 46,94 . Changes in strength data resulting from the additional protein intervention were extracted from 50 studies testing 2283 subjects for lower‐body strength 33,36–39,43,44,47–49,52–58,61–65,67–70,72,74–78,82,84,86,88–92,94,96,100–104 and only three studies with intervention groups without RE 41,99,105 . Thirty‐four studies tested bench‐press strength 33,36–38,43,47–49,53–55,62–65,67,68,70,72,74,75,77,78,82,84,86–88,90,91,93,95,96,99 with 1049 subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recommended that older adults consume ≥ 0.4 g/kg per meal and 1.2-1.6 g/kg per day to induce muscle protein synthesis saturation to thus support muscle function [41]. Among the included studies, two studies provided an appropriate amount of protein (10 g milk protein and 0.5 g/kg whey protein) three times a day, taking into account frequency and distribution [21,25,26]. Other studies provided 10.1 g-25 g protein once a day [44][45][46][47] or 20 g ~ 35 g protein 3 times a week on the days exercise was performed [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Several evidencebased systematic reviews and meta-analyses of RCTs have shown that exercise affects muscle mass, strength, and physical performance [17,20]. For optimal effects, multimodal exercise combined with moderate-to high-intensity progressive resistance training and functional balance and mobility training at least twice a week for 30-45 minutes per session is recommended [19,21].…”
Section: Introductionmentioning
confidence: 99%